Recompositions et dynamiques de l'enseignement arabo-islamique au Niger : le cas de Zinder - Mahamane Mahaboubou Malam Sani (Les éditions de la Maison des sciences de l'Homme, 2017)
This article draws on a doctoral study in sociology defended in October 2016. It addresses the reshaping of Arab-Islamic education in Zinder, a city located at 1000 km Est of Niamey. While public non-confessional education remains the main reference for parents looking at school as a way to improve their children standards of leaving, it has been much criticized for its lack of efficiency. Meanwhile Arab-Islamic education greatly benefited from the dynamics of the Islamic sector observed since the beginning of the 90's. New pedagogical approaches were introduced in Muslim schools by religious actors who call themselves reformists, while the State tried to upgrade Arab-Islamic education in order to integrate it in the national school system.